Fabrication of graphene/single wall carbon nanotubes/polyaniline composite gels as binder‐free electrode materials. Issue 3 (28th September 2018) - Du, Xiangxiang; Luo, Fubin; Guo, Yuyue; Zhu, Qingqing; Xiao, Fei; Wu, Kun; Lu, Mangeng
ABSTRACT: A three‐dimensional (3D) graphene‐based hydrogels system containing one‐dimensional (1D) carbon material‐single wall carbon nanotubes (SWCNTs) and pseudocapacitor material‐polyaniline (PANI) was prepared by combination of cross‐linking, reduced and in situ polymerization. The polyaniline nanoparticles were combined with the reduced graphene sheet by π‐π conjugation. The as‐perpared composite gels could be directly used as electrode materials without binders. Due to the synergistic effect between SWCNTs, graphene sheet and PANI, the graphene/single wall carbon nanotubes/polyaniline (GH/SWCNTs/PANI) composite gel shows the enhanced electrochemical performances. The resultant GH/SWCNTs/PANI gel electroactive material shows a gravimetric specific capacitance of 145.4 F/g at 0.5 A/g and has improved 45% compared with initial graphene hydrogel (GH) at the same current density. And it keeps high retention of 98.8% of the initial capacity after 10, 00 charge/discharge cycles at high current density of 10 A/g. The great cycle stability achieved is fundamentally attributed to the support of graphene sheet and single wall carbon nanotubes, which favors stress distribution and charge transfer during the longtime charge/discharge process. The graphene‐based hydrogels could be a potential applicant for high rate charge/discharge applications. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 46948. Abstract :